Mobilisasi Dini Dan Perawatan Luka Pasca Arthrodesis Lutut Pada Kondrosarkoma Tibia: Laporan Kasus - Fajar, Kana; Kurniawan, Titis; Pratiwi, Sri Hartati; Maryam, Nina (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2026)
Background: Proximal tibial chondrosarcoma is a malignant bone tumor requiring wide resection and often causing challenges in wound management and lower-limb functional recovery. In resource-limited healthcare settings, knee arthrodesis remains an important limb-salvage procedure when endoprosthesis reconstruction is unavailable. However, evidence regarding nursing-based postoperative wound care and early mobilization remains limited. Objective: This case report describes the implementation of an evidence-based nursing approach integrating early mobilization with objective monitoring of wound healing and functional outcomes following knee arthrodesis. Case: A 40-year-old male with grade 2 proximal tibial chondrosarcoma underwent wide resection followed by knee arthrodesis using plate–screw fixation and bone cement. Postoperatively, the patient experienced massive bleeding resulting in anemia, leucocytosis, severe lower-limb muscle weakness, restricted mobility, and partial functional dependence. Intervention and Outcomes: Daily nursing assessments were conducted using the Bates–Jensen Wound Assessment Tool (BWAT) and the Modified Iowa Level of Assistance Scale (mILOA). Early mobilization was initiated on postoperative day two. Over 19 days, BWAT scores improved from 24 to 13 without wound dehiscence, accompanied by increased functional mobility and reduced dependence from partial assistance to minimal assistance. Conclusion: Early mobilization combined with BWAT- and mILOA-based monitoring may provide a safe, practical, and sustainable nursing strategy to support wound healing and functional recovery after knee arthrodesis in resource-limited settings.